Three new species of Tenuipalpus Donnadieu (Acari, Tenuipalpidae) from the State of São Paulo, Brazil - Feres, Reinaldo J. F. [UNESP]; Hernandes, Fábio A. [UNESP] (My University, 2006)
Three new species of Tenuipalpus, T. carlosflechtmanni n. sp., T. moraesi n. sp. and T. ariauae n. sp., collected on wild plants in Brazil, are described and illustrated. Copyright © 2006 Magnolia Press.
Keywords: Acari; False spider mites; Taxonomy; Tenuipalpidae; Tenuipalpus